2020
DOI: 10.31674/mjn.2020.v11i04.001
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Whatsapp Mobile Learning on the Academic Achievement Among Nursing Students

Abstract: The use of mobile learning activities in learning and teaching online course is an innovative educational technology in higher education. The study seeks to explore the impact of using WhatsApp mobile learning on academic achievement among nursing students at ILKKM Kubang Kerian (Kejururawatan), Kelantan. Methodology: This study involved a total of 49 nursing students who had been chosen by the "Purposive Sampling". The pilot study was done in order to determine the reliability and suitability of the questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
0
0
Order By: Relevance
“…The findings are in line with Latif who reported that academic achievement has improved using online learning among student nurses in Malaysia. 11 In contrast, Hjorth-Johansen et al 12 revealed that there was no significant difference in academic achievement between classroom learning and e-learning nursing.…”
Section: Literature Reviewmentioning
confidence: 96%
“…The findings are in line with Latif who reported that academic achievement has improved using online learning among student nurses in Malaysia. 11 In contrast, Hjorth-Johansen et al 12 revealed that there was no significant difference in academic achievement between classroom learning and e-learning nursing.…”
Section: Literature Reviewmentioning
confidence: 96%